2017
DOI: 10.1007/s12016-017-8609-4
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular B Lymphocyte Signalling and the Regulation of Humoral Immunity and Autoimmunity

Abstract: B lymphocytes are critical for effective immunity; they produce antibodies and cytokines, present antigens to T lymphocytes and regulate immune responses. However, because of the inherent randomness in the process of generating their vast repertoire of antigen-specific receptors, B cells can also cause diseases through recognizing and reacting to self. Therefore, B lymphocyte selection and responses require tight regulation at multiple levels and at all stages of their development and activation to avoid disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 313 publications
(260 reference statements)
0
28
0
Order By: Relevance
“…Autoantibody production can occur due to failures in these checkpoints or in T cell self-tolerance mechanisms. Variants in multiple genes are implicated in increasing the likelihood of checkpoint failure and of autoantibody production occurring (Goodnow et al, 2010;Nemazee, 2017;Taher et al, 2017).…”
Section: Natural Antibody and ''Innate Memory''mentioning
confidence: 99%
“…Autoantibody production can occur due to failures in these checkpoints or in T cell self-tolerance mechanisms. Variants in multiple genes are implicated in increasing the likelihood of checkpoint failure and of autoantibody production occurring (Goodnow et al, 2010;Nemazee, 2017;Taher et al, 2017).…”
Section: Natural Antibody and ''Innate Memory''mentioning
confidence: 99%
“…B cells play an important role in the adaptive immune system by secreting antibody to identify and neutralize invading pathogens like bacteria and viruses. In addition, B cells also have antibody‐independent functions, including antigen presentation, secreting cytokines, as well as regulatory and effector activity . However, although B cell is an important component of immune system, its function during the natural history of chronic HBV infection remains obscure and has not been paid much attention to.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, B cells also have antibodyindependent functions, including antigen presentation, secreting cytokines, as well as regulatory and effector activity. [8][9][10] However, although B cell is an important component of immune system, its function during the natural history of chronic HBV infection remains obscure and has not been paid much attention to. Previous studies patients with CHB.…”
Section: Introductionmentioning
confidence: 99%
“…inhibition of β‐catenin signalling, inhibition of tyrosine kinase and B‐cell depletion . The several studies demonstrated that the contribution of B cell and T cell in SSc development and pathogenesis. In addition to the acquired immunological reaction on SSc, the role of the innate immune system in the pathogenesis of SSc is now being increasingly recognized .…”
Section: Introductionmentioning
confidence: 99%